Creche: do direito ?? educa????o ?? judicializa????o da vaga - Poloni, Maria Jos?? (2017)
The right to education appears in legal texts, especially in the Federal Constitution of Brazil of 1988, in the Statute of the Child and Adolescent (ECA), of 1990, and in the Law of Directives and Bases of National Education (LDB) of 1996. However, there is still a meaningful number of children, adolescents and young people, totally or partially excluded from the formal education system. This fact becomes more evident in early childhood education; within the age group from zero to three years old, that is, in kindergarten. Considering that early childhood education is the first stage of basic education, which, besides being a social right, is a universal right, a duty of the State and the family, this thesis has the objective of analyzing and understanding the reasons for the mismatch between legal texts and the reality in childhood education. Particularly in the context of kindergarten, in the Mau?? district, leading to the judicialization of education at this stage. The scope of this research comprises, in the bibliographic context, research and study on the theme of education as a right, the main official texts on the legislation of the subject, and, empirically, data and information collected in a municipal school of early child education. It considers the discourse of the different agents involved in this reality (mothers of children at day-care centers, teachers and school administrators) as well as data obtained at the Municipal Department of Education regarding registration and legal actions, filed by parents, to obtain a vacancy in the day-care center. The theoretical reference of this research is based on authors who have developed studies focused on the right to education and its viability, thinkers who identified with the emancipating approaches to education, among them Paulo Freire and scholars of child education, specifically of early child education. This research develops from quantitative and qualitative approaches, operating with both official data (Municipal Secretary of Education, Federal Government and Public Ministry) as well as information from protagonists of the school reality. According to the data analysis obtained so far, it is quite clear that, since LDB / 96, when early childhood education was included in the basic system, this stage of education gained greater visibility and became the target of public policies. However, there is still not enough amount of schools to care for children between zero and three years of age. Thus, as well as the legal text, which states that education is a universal right, a real text, noticed by a movement of the organization of society, through a claim with the public institutions, is being developed those who have had their rights historically denied.